2006
DOI: 10.1007/s10974-005-9035-4
|View full text |Cite
|
Sign up to set email alerts
|

Titin PEVK segment: charge-driven elasticity of the open and flexible polyampholyte

Abstract: The giant protein titin spans half of the sarcomere length and anchors the myosin thick filament to the Z-line of skeletal and cardiac muscles. The passive elasticity of muscle at a physiological range of stretch arises primarily from the extension of the PEVK segment, which is a polyampholyte with dense and alternating-charged clusters. Force spectroscopy studies of a 51 kDa fragment of the human fetal titin PEVK domain (TP1) revealed that when charge interactions were reduced by raising the ionic strength fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 48 publications
1
38
0
Order By: Relevance
“…However, these studies were performed in intact, contracting muscle. Consequently, the results might be confounded by the presence of calcium cycling: calcium binds to the PEVK spring‐domain of titin, changing its stiffness,15, 16, 17 and titin‐based stiffness modulates contractility20, 41, 42, 43, 44 which in turn might affect muscle growth. The importance of the current findings is that they show that the effects of titin‐based mechanosensing occur independent of contractile activity, and can be ascribed to titin's elastic properties.…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies were performed in intact, contracting muscle. Consequently, the results might be confounded by the presence of calcium cycling: calcium binds to the PEVK spring‐domain of titin, changing its stiffness,15, 16, 17 and titin‐based stiffness modulates contractility20, 41, 42, 43, 44 which in turn might affect muscle growth. The importance of the current findings is that they show that the effects of titin‐based mechanosensing occur independent of contractile activity, and can be ascribed to titin's elastic properties.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation sites are commonly found in intrinsically disordered regions of proteins, with phosphorylation having both local effects on the order of secondary structures and global effects on the orientation of tertiary states (32)(33)(34). Such structural rearrangements can result in changes in the affinity for binding partners (33,35) and/or the mechanics of the phosphoprotein in the bound state (32,36).…”
Section: Discussionmentioning
confidence: 99%
“…Elsewhere, we have proposed that the PEVK segment is a polyampholyte that wraps into a nanogel via ion pair interactions and that the mechanically induced unraveling and wrapping forms the basis of PEVK elasticity (26). In this context of ligand/receptor interaction, the accessibility of SH3-containing protein to the ligand is perhaps controlled by how the PEVK nanogel alters the pore size distribution in response to mechanical stress.…”
Section: Pevk and Polyproline Regions As A Force-sensitive Controllermentioning
confidence: 99%
“…The facile interconversion of these conformational states under subtle environmental conditions such as temperature, ionic strength, and solvent polarity has revealed that the titin PEVK segment is conformationally malleable, without involving proline trans/cis isomerization. The elasticity of PEVK also varies with ionic strength, where the elasticity has been measured to either decrease (26,27) or increase (28) with increasing ionic strength. This behavior implies that ionic interactions within the PEVK segment play an important role in the ensemble average of the polypeptide configuration and therefore the relative entropic and enthalpic contributions to molecular elasticity.…”
mentioning
confidence: 99%
See 1 more Smart Citation